Reassessing Tajdid al-Nikah: Maqasid al-Shariah and Legal Status of Illegitimate Children in Central Lombok - Doni Azhari; Asmuni Asmuni; Khoiruddin Nasution (Justicia Islamica, 2025)
The practice of tajdid al-nikah (renewal of marriage) within the framework of Maqhasid Sharia presents significant issues in Islamic law, particularly concerning legitimizing the lineage (nasab) of children born outside of marriage. In Islamic law, a couple involved in adultery can validate their relationship post-birth of a child through tajdid al-nikah to establish legal paternity. Although this practice aims to fulfill maqasid al-shariah objectives, such as preserving religion and lineage, it introduces various social, ethical, and legal challenges. This study aims to evaluate the social, moral, and legal ramifications of tajdid al-nikah and assess its alignment with the core principles of maqasid al-shariah, namely, the preservation of religion, lineage, intellect, and property. Additionally, it examines local perceptions in Central Lombok regarding tajdid al-nikah and the Islamic understanding of children born outside of marriage. The research employs a combination of literature review, field investigations, document analysis, and interviews with Islamic law experts and local religious leaders, using an analytical descriptive method grounded in Islamic legal principles. The findings reveal the complexities associated with tajdid al-nikah. While the practice supports maqasid al-shariah goals such as preserving lineage and religion, issues such as the ambiguity in confirming legitimate lineage and potential social repercussions highlight the need for further study. This research advocates for continued exploration and discussion on how tajdid al-nikah can be effectively integrated within an Islamic legal framework that respects maqasid al-shariah values, justice, legal certainty, and social welfare.